2017
DOI: 10.1177/1010428317697547
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of potential biomarkers for cervical squamous cell carcinoma and human papillomavirus infection

Abstract: It is known that high-risk human papillomavirus infection is the main etiological factor in cervical carcinogenesis. However, human papillomavirus screening is not sufficient for early diagnosis. In this study, we aimed to identify potential biomarkers common to cervical carcinoma and human papillomavirus infection by proteomics for human papillomavirus-based early diagnosis and prognosis. To this end, we collected 76 cases of fresh cervical tissues and 116 cases of paraffin-embedded tissue slices, diagnosed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 98 publications
(126 reference statements)
2
16
0
1
Order By: Relevance
“…Qing et al conducted a proteomic identification of potential biomarkers for cervical squamous cell carcinoma and found that MCM5 might be important in cervical cancer. 38 In this study, we observed that MCM5 was an independent prognostic biomarker in cervical squamous cell carcinoma, and the results showed that MCM5 expression decreases as stage increases. A possible reason might be that MCM5 was present throughout the cell cycle of proliferating cells but not in nonproliferating quiescent cells.…”
Section: Discussionmentioning
confidence: 69%
“…Qing et al conducted a proteomic identification of potential biomarkers for cervical squamous cell carcinoma and found that MCM5 might be important in cervical cancer. 38 In this study, we observed that MCM5 was an independent prognostic biomarker in cervical squamous cell carcinoma, and the results showed that MCM5 expression decreases as stage increases. A possible reason might be that MCM5 was present throughout the cell cycle of proliferating cells but not in nonproliferating quiescent cells.…”
Section: Discussionmentioning
confidence: 69%
“… 19 Therefore, it is vital to dissect the molecular mechanisms underlying the initiation and progression of HCC. Recent studies showed an oncogenic function of ENO1 in various cancers, with high expression levels observed in cervical squamous cell carcinoma, 13 pancreatic cancer, 11 , 15 breast cancer, 20 non-small cell lung cancer (NSCLC), 21 nasopharyngeal carcinoma, 22 and HCC. 16 , 17 We analyzed the expression level of ENO1 on multiple HCC samples using the gene expression data available in TCGA and GEO HCC databases and HCC TMA.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 In addition to glucose metabolism, ENO1 is involved in autoimmune response, hypoxia endurance, and growth regulation. 10 – 12 Recent studies have correlated ENO1 with tumorigenesis and cancer progression 13 – 15 and have also shown its specific involvement in multiple signaling pathways in HCC cells. 2 , 16 , 17 However, the clinical significance and diagnostic value of ENO1 in HCC remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al ( 14 ) found that hnRNPA1 protein was overexpressed in lung cancer (LC), whereas knockdown of hnRNPA1 inhibited cell viability and colony formation of LC cells and arrested the cell cycle in the G0/G1 phase. Furthermore, another study revealed the upregulated expression and aberrant cytoplasmic localization of hnRNPA1 in cervical squamous cell cancer ( 15 ). Recently, hnRNPA1 has emerged as a plausible GC biomarker ( 16 ).…”
Section: Introductionmentioning
confidence: 99%